(3GdSge GdUGFH aj bHV Ojf GdZGFHs - (3Ydj Hf YHO GdcGaj Hf Ydj Hf JeGe GdSHcj GdCfUGQj GdNRQLj, CHh GdMSf, Jbqj GdOjf,J (B756 (3g` s
(3ChdgG (B:s
(3GdMeO ddg hMOg CeG HYO abO SFd Yf TNU Qgf YjfkG HOjf eDLd , hZGH ef dg GdOjf , aCMVQ GdQGgf GdeOjhf GdOjf hgh OQGe dGjTa MedgG s
(3BNQgG (B:s
(3hJHjf Cf cdGe GdQGaYi ai HGH GdhOjYI hJQLjMjg YOe hLhH bHhd GdOjf Ydi dGZGFH , eMehd YdieG EPG de jcf Hg Qgf hGdgd JYGdi CYde Je hddg GdMeO s
(3Vef eLehY , JQJjHgG (B: (3ef U (B30 - (3U(B41s
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV cdeGJgG HGdMeQIs
(3YdjgG JUMjMGJ s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdabg GdTGaYjs